Hubungan Kualitas Aplikasi dan Kemudahan Penggunaan dengan Kepuasan Pengguna Aplikasi Jamsostek Mobile (JMO) pada Karyawan PT. Tanduk Perkasa Unit Pemeliharaan, Operasi dan Energi Primer - Putri Fera Yolanda; Siti Maisyaroh Fitri Siregar; Darmawan Darmawan; Fakhrullradhi Fakhrullradhi; Mardhi Fadillah (KOLONI, 2026)
The digital transformation of employment social security services through the Jamsostek Mobile (JMO) app requires a high-quality, user-friendly app to improve user satisfaction. At PT. Tanduk Perkasa’s Maintenance, Operations, and Primary Energy Unit, the JMO usage rate remains relatively low (65%); therefore, this study aims to analyze the relationship between app quality and ease of use and user satisfaction with the JMO app. This study employed a quantitative approach with a cross-sectional design. The population consisted of 113 employees who use JMO, with a sample of 88 respondents determined using the Slovin formula (5% margin of error). The sampling technique was based on a contrastive approach. Data were collected using questionnaires and interviews, while data analysis was performed using the Chi-Square test. The results of the descriptive analysis show that most respondents found the Jamsostek Mobile (JMO) app difficult to use, with 60.2% stating that the app’s quality did not meet their expectations and a relatively low user satisfaction rate of 57.9%. These findings indicate that the implementation of JMO digital services at PT. Tanduk Perkasa’s Maintenance, Operations, and Primary Energy Unit has not yet been optimal. The results of a bivariate analysis using the Chi-Square test show a significant relationship between ease of use and satisfaction with the JMO application (p = 0.000), as well as between application quality and satisfaction with the JMO application (p = 0.006). It was concluded that the better the quality of the application and the easier it is to use, the higher user satisfaction will be. Therefore, system improvements, interface simplification, enhanced application stability, and ongoing outreach are needed to increase satisfaction and the effectiveness of JMO usage.